The City as Architecture - Wolfrum, Sophie; Janson, Alban (Birkhäuser, 2019)
Architecture creates complex spatial situations that are the subject of urban design. Design uses a repertoire of specific architectural means in a creative way, resulting in cities that can be lived in and perceived in their three-dimensional experience. The current book, an extended new edition of Architecture of the City (2016), describes the repertoire with which architecture and design regain an entry to urbanistics. It pleads for an "architectonic turn" in urbanistics - a demand to finally comprehend the city architecturally: the issue is not just about buildings in the city, but about architecture of the city as a whole, as is clearly expressed in the new title of City as Architecture.